Combined GPS, BeiDou, Galileo, and QZSS single-epoch, single-frequency RTK performance analysis - Odolinski, R.; Teunissen, Peter; Odijk, Dennis (2016)
© Springer International Publishing Switzerland 2015. In this contribution we will focus on instantaneous (single-epoch) single-baseline Real- Time Kinematic (RTK) combining four CDMA satellite systems. We will combine the Chinese BeiDou, the European Galileo, the American GPS and the Japanese QZSS system. To further strengthen the underlying model and maximize the redundancy, attention will be given to overlapping frequencies between the systems. With calibrated Inter System Biases (ISBs), it enables one to use a common pivot satellite between the respective systems when parameterizing the double-differenced ambiguities. We make use of the LAMBDA method for ambiguity resolution, and the performance is evaluated by ambiguity success-rates and by comparing the estimated positions to very precise benchmark coordinates. This will be based on various elevation cut-off angles so as to mimic conditions with obstructed satellite visibility (such as in urban canyons). It will be shown by how much the increased strength of the combined models allow for improved ambiguity resolution performance and positioning robustness over the single-systems.